Stem Cell Neurodevelopmental Solutions for Restorative Treatments of the Human Trunk and Spine - Olmsted, Zachary T.; Paluh, Janet L. (Frontiers in Cellular Neuroscience, 2021)
The ability to reliably repair spinal cord injuries (SCI) will be one of the greatest human achievements realized in regenerative medicine. Until recently, the cellular path to this goal has been challenging. However, as detailed developmental principles are revealed in mouse and human models, their application in the stem cell community brings trunk and spine embryology into efforts to advance human regenerative medicine. New models of posterior embryo development identify neuromesodermal progenitors (NMPs) as a major bifurcation point in generating the spinal cord and somites and is leading to production of cell types with the full range of axial identities critical for repair of trunk and spine disorders. This is coupled with organoid technologies including assembloids, circuitoids, and gastruloids. We describe a paradigm for applying developmental principles towards the goal of cell-based restorative therapies to enable reproducible and effective near-term clinical interventions.